(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the article the process of anaerobic digestion of sewage sludge in bioaerator was studied. The work was carried out on the basis of laboratory of Jizzakh city sewage treatment plant named "Uchtepe". As a result of studying this work, data on biogas yield and composition of sewage sludge were obtained. Special attention is paid to the development of technologies for biogas production. A promising direction of sewage sludge processing is biochemical conversion by anaerobic digestion in bioaerators.